Next generation polyurethanes for enhanced durability pre-finished architectural steel products. - Jenet Wray (2008)
This research has focussed on the photo-oxidation of polyurethane coatings with aim to identify formulations with enhanced durability. The stability of a coating against the effects of environmental ultraviolet (UV) light poses a challenge to coating manufacturers particularly since almost all coatings contain titanium dioxide (TiO2) as a pigment. It is widely acknowledged that TiO2 can become photoactivated by incident UV light, causing initiation of free radicals which under go reactions with the polymeric matrix and result in degradation of the coating. Previous research has identified a novel accelerated weathering test that allows quantification of coating photo-oxidation by measurement of evolved carbon dioxide (CO2) gas using a Fourier Transform Infrared (FTIR) spectrometer. The FTIR flat panel irradiation apparatus was used in conjunction with QUV A and xenon arc weathering in order to assess the durability of polyurethane coatings. Out of a range of TiO2 pigments Tronox R-KB-4 was the most stable for production of polyurethane coatings. It was found that alterations to the coating formulation, namely replacement of the standard durability polyester with one expected to improve UV durability did not provide the improvements anticipated. The polyurethane formulation containing a polyisocyanate cross-linker based on a combination of hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI) showed the best durability and most promise for improvement of commercial coatings. The effects of additives commonly used in commercial polyurethane coatings were investigated. It was found that although the addition of coloured pigments and texturing agents commonly affected coating durability, the majority of increase in coating degradation was due to the unstable nature of organic matting and texturing agents. Finally it was shown that the dispersion of a TiO2 pigment within polymeric matrix can significantly affect is durability. Coatings containing poorly dispersed TiO2 pigments showed a significant reduction in durability compared to those containing an optimum dispersion of TiO2.